Understanding In-Situ Use of Commonly Available Navigation Technologies by People with Visual Impairments - Kameswaran, Vaishnav; Fiannaca, Alex; Kneisel, Melanie; Karlson, Amy; Cutrell, Ed; Morris, Meredith Ringel (ASSETS 2020, 2020)
Despite the large body of work in accessibility concerning the design of novel navigation technologies, little is known about commonly available technologies that people with visual impairments currently use for navigation. We address this gap with a qualitative study consisting of interviews with 23 people with visual impairments, ten of whom also participated in a follow-up diary study. We develop the idea of complementarity first introduced by Williams et al. and find that in addition to using apps to complement mobility aids, technologies and apps complemented each other and filled in for the gaps inherent in one another. Furthermore, the complementarity between apps and other apps/aids was primarily the result of the differences in information and modalities in which this information is communicated by apps, technology and mobility aids. We propose design recommendations to enhance this complementarity and guide the development of improved navigation experiences for people with visual impairments.